RELIGIOUS MODERATION: A COMPARATIVE STUDY OF THE VIEWS OF AL-AZHAR AND THE MINISTRY OF RELIGION OF THE REPUBLIC OF INDONESIA - Yusuf Rahim; Andi Fadhil; Achmad Abubakar; Kurniati; Abd. Rahman (Universitas Islam Negeri (UIN) Mataram, 2024)
This research aims to determine how the view of the Al-Azhar interpretation book and the Ministry of Religion of the Republic of Indonesia relates to religious moderation. These two interpretations both discuss the notion that Muslims have a unique concept of thinking in religious matters. This research is a field research (field research). This study's data includes descriptive qualitative research that explains and describes Religious Moderation: A Comparative Study of the Views of Al-Azhar and the Ministry of Religion of the Republic of Indonesia.